Volunteering for otter conservation in Nepal: communicating with local communities - Thapa, Sanjan; Pun, Tejab; Adhikari, Dipendra (Journal of Wetlands Ecology, 2020)
Amongst three species of otters, the Asian Small-clawed Otter has not been recorded since Hodgson (1839). Since 1991, the Eurasian Otter has neither been photographed nor sighted in the country. Recently, the Smooth-coated Otter has been reported only from Bardia National Park and its west. In this chaotic situation, a volunteer project was initiated for otter conservation in Nepal three years ago. 1000 copies of an otter conservation awareness poster were printed in 2017 and a second set of posters in 2019. Posters were distributed to local communities while communicating with the local people along the way and during stays. Thus far, we have conducted awareness activities at selected sites in nine districts and four protected areas. Over three years, we have talked with more than 2000 local people about otters and disseminated more than 1300 posters. At all sites, local communities responded that they had not seen otters for 20 to 30 years or more and for the last 10 years, even in protected areas. However, there are hopes that the last scarce individuals or populations of otters remain at very few sites. Overfishing, river poisoning and pollution, hydropower dams and station construction, and sand and pebble extraction from rivers, are the major causes for depletion of otters in these areas. In the past, trapping by Tibetans for otter pelts and by nomads from the plains of Nepal and India were major causes for population declines. In conclusion, we convey a conservation message that humans must learn to co-exist with otters if the species are to survive.